Peran Bahasa Indonesia Dalam Meningkatkan Daya Saing Penjualan Dan Promosi UMKM Home Cookie And Snack - Dali, Meilina Widya; NTani, Riston; Jon, Sandi; Ibrahim, Zilzilia; Ibrahim, WinaryoWanto; Suwandana, Jessica Amelia Putri; Kurnia, Kurnia; Madjid, Putri; Dama, Sri Kartika; Kalamu, Siti Kamaria; Latidi, Muhammad Yusuf; Gobel, Nazwa Akhiria; Podungge, Tri Agustina; Usman, Mochamad Yuma Fadhila (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the role of the Indonesian language in enhancing the sales competitiveness and promotional effectiveness of the Home Cookies and Snack MSME. The research focuses on the forms of Indonesian language use in promotional activities and its contribution to consumer attractiveness and increased product sales. A qualitative approach was employed, with the research conducted at the Home Cookies and Snack MSME located on Jalan 23 Januari, Ipilo Subdistrict. Data were collected through observation, in-depth interviews, and documentation involving the business owner as the main informant, as well as employees as supporting informants who were directly engaged in promotional and customer service activities. The findings indicate that the use of communicative, polite, and persuasive Indonesian language plays a significant role in conveying product information, building consumer trust, and creating emotional closeness that encourages purchase intention and repeat buying. Indonesian language functions not only as a medium for delivering promotional messages but also as a means of shaping business image and identity. However, the use of promotional language remains largely spontaneous and has not been systematically designed as a long-term marketing strategy. This study concludes that optimizing the planned and consistent use of the Indonesian language can serve as an effective strategy to improve MSME sales competitiveness.